Assessing The Factors That Influence The Acceptance And Adoption Of The Use Of New Performance Technology Systems In Indonesia Drugstores By Pharmacists Using The Utaut-2 Model - Dini Rohmatul Insani; Richard Sutejo (Journal of Strategic Innovation and Business Management, 2025)
The rapid acceleration of digital transformation, especially during the COVID-19 pandemic, has drastically reshaped consumer behavior and necessitated adaptation within the healthcare sector, including pharmacy retail. Independent drugstores in Indonesia face mounting pressure to digitalize their operations to meet evolving customer demands, particularly through the adoption of integrated pharmacy operational systems (e-iPOS). This research examines the factors influencing pharmacists’ acceptance and use of such digital systems using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT-2) model. A structured questionnaire was distributed to pharmacists across Indonesia, with 202 valid responses analyzed through structural equation modeling using SmartPLS. The study reveals that social influence, price value, and habit significantly affect pharmacists’ behavioral intention to adopt e-iPOS, with habit also directly influencing actual usage behavior. Surprisingly, traditional constructs like performance expectancy and effort expectancy were not significant predictors. These findings underscore the importance of peer influence, perceived value, and behavioral habituation in driving technology adoption in the pharmaceutical sector. The results provide actionable insights for developers of digital pharmacy platforms and health policymakers aiming to support digital transformation in independent pharmacies, particularly through tailored training, pricing strategies, and advocacy campaigns involving key opinion leaders in the pharmacy community.